Pengaturan Kecepatan Motor Induksi 3fasa Dengan Mengatur Frekuensi Menggunakan VSD di PERUMDAM Tirta Madani Serang - Ihsan Faturrohman; Mohammad Fatkhurrokhman (Fakultas Teknik Universitas Cenderawasih, 2023)
The frequency setting is VSD (variable speed drive) or inverter. In controlling the speed of a 3-phase induction motor using a VSD or inverter, the PWM (pulse width modulation) method is used. PWM is a method of manipulating the signal width, which is described by pulses in one period. In collecting data, the methods used are observation, interviews, documentation, and literature studies. The data obtained in the observation are the values of frequency, voltage, and current at the output of the VSD, which goes to the source of the 3-phase induction motor. The results obtained from setting the motor speed by setting the frequency at 25 Hz are 1500 rpm, 30 Hz is 1800 rpm, 35 Hz is 2100 rpm, 39.1 Hz is 2346 rpm, and 40 Hz is 2400 rpm. By adjusting the input frequency to a 3-phase induction motor using a VSD or inverter, it can be concluded that the higher the frequency, the faster the rotation speed of the pump motor, and the resulting water discharge in sucking water will also be greater.